Analysis of Tourists’ Preferences Toward Alternative Accommodation in North Kuta, Bali - Giarike Kentjana; Anak Agung Nyoman Sri Wahyuni; Dinar Sukma Pramesti (Jurnal Pariwisata Nusantara (JUWITA), 2026)
Purpose: This study aims to identify tourists' characteristics and analyze their preferences toward alternative accommodation in North Kuta, Badung, Bali, where the rapid growth of villas, homestays, and guest houses has intensified competition within the accommodation sector. Method: This study adopted a descriptive quantitative approach supported by qualitative interviews. Data were collected from 122 questionnaire respondents and eight interview informants using purposive sampling. Quantitative data were analyzed using descriptive statistics, while qualitative data were analyzed thematically to support the interpretation of the findings. Results: The findings indicate that users of alternative accommodation are predominantly domestic tourists, belong to productive age groups, possess relatively high educational backgrounds, and are mainly employed as private employees or entrepreneurs. Villas are the most preferred accommodation type. Tourists prioritize functional accommodation attributes, particularly comfort, tranquility, privacy, and accessibility, whereas price, facilities, and location serve as supporting considerations. Unique and authentic experiences function as complementary values that enhance the accommodation experience rather than the primary basis for accommodation choice. Contribution: This study contributes to the tourist behavior literature by demonstrating that accommodation preferences are shaped by the interaction between tourist characteristics and benefit-seeking behavior. The findings extend behavioral segmentation theory by showing that tourists prioritize functional accommodation attributes before experiential values when selecting alternative accommodation. The results also provide practical insights for accommodation providers and destination managers in developing accommodation products and marketing strategies that better respond to tourists' preferences.